Endogenous type I interferons and their regulators in multiple sclerosis. (January 2017) - Miyazaki, Yusei; Niino, Masaaki
Abstract: Multiple sclerosis (MS) is an autoimmune disease of the central nervous system. In the past few decades, several disease‐modifying drugs including interferon (IFN)‐β have become available for treating MS. IFN‐β belongs to the type I IFN family, and thus is an endogenous molecule whose primary role is thought to be host defense against viruses. In addition, type I IFN are constitutively produced at low amounts and involved in the homeostasis of various tissues. In contrast, it is suggested that type I IFN play a pathogenic role in other autoimmune diseases, such as lupus. Several lines of evidence from studies using MS samples and animal models suggest the protective role of endogenous type I IFN in MS. Correspondingly, MS patients with a higher endogenous type I IFN signature show lower disease activity. Paradoxically, these patients have been shown to respond poorly to IFN‐β therapy. In addition, an animal model with a defective regulatory mechanism in type I IFN signaling has been shown to develop augmented central nervous system autoimmunity, suggesting that type I IFN responses need to be appropriately regulated in MS. Multiple endogenous molecules participate in the regulation of type I IFN responses, but their roles in MS have not been studied extensively. Further study delineating the role of endogenous type I IFN and their regulatory mechanisms in MS should enhance our understanding of the disease, and could lead to improvements in the therapeutic effects of IFN‐β in MS.